2012
DOI: 10.1007/s12253-012-9565-1
|View full text |Cite
|
Sign up to set email alerts
|

Significance of AgNORs and Ki-67 Proliferative Markers in Differential Diagnosis of Thyroid Lesions

Abstract: We aimed to assess the utility of quantitative analysis of AgNORs and Ki67 labeling index (LI) in the differential diagnosis of different thyroid lesions. This study included: 25 papillary carcinomas, 7 follicular carcinomas, 21 follicular adenomas and 27 nodular goiters. Using a semiautomatic image analysis system, Ag NORs parameters were measured and calculated including: total area of AgNORs, mean Ag NOR number in nuclei, nuclear area, mean area of AgNOR dots per each nucleus, number of central and marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
8
2
2
Order By: Relevance
“…In this study, although the absolute value of expression intensity and positive rate of Ki67 in PTMC was not very high, the expression intensity was below 25%, but it had statistical significance with the differences between PTMC and benign lesions with papillary hyperplasia. Some study also confirmed that Ki67 expression is beneficial for the differential diagnosis of thyroid papillary carcinoma (Aiad et al, 2013).…”
Section: Discussionmentioning
confidence: 70%
“…In this study, although the absolute value of expression intensity and positive rate of Ki67 in PTMC was not very high, the expression intensity was below 25%, but it had statistical significance with the differences between PTMC and benign lesions with papillary hyperplasia. Some study also confirmed that Ki67 expression is beneficial for the differential diagnosis of thyroid papillary carcinoma (Aiad et al, 2013).…”
Section: Discussionmentioning
confidence: 70%
“…Since then, this finding has been confirmed by several other groups [22][23][24][25][26][27][28][29][30]. The widespread application of the technique has been hindered by the relatively wide overlap between AgNOR values of the benign and malignant groups [31].…”
Section: Variablementioning
confidence: 67%
“…Індекс ПА як кількісний критерій досить активно застосовується в мамології при оцінці агресії злоякісного процесу. ПА пухлинних клітин при раку ЩЗ досить активно вивчається в країнах Західної Європи, США, Ро-сії та Японії [15]. Багато досліджень демонструють високий рівень експресії при злоякісній патології ЩЖ, зокрема при папілярному раку ЩЗ, а також як прогностично несприятливий фактор при ди-ференціальній діагностиці ФА і ФРЩЗ [16,17].…”
Section: обговоренняunclassified